Two-way coupled CFD fire and thermomechanical FE analyses of a self-supporting sandwich panel façade system. (April 2019) - de Boer, J.G.G.M.; Hofmeyer, H.; Maljaars, J.; van Herpen, R.A.P.
Abstract: A self-supporting sandwich panel façade system under fire is studied. First, a thermomechanical FE model, which comprises the complete façade system, and incorporates material degradation and geometrical nonlinear behaviour except for the insulation material and connections, is loaded by a fire temperature curve. Eurocode design rules then predict the screw connections of a sandwich panel will fail in shear. Secondly, an existing programme, FDS-2-Abaqus, is extended to allow its two-way coupled analyses, in which CFD fire simulations are updated for changes in the thermomechanical FE model, to be applicable to the façade system. Again, these simulations show the shear failure of the screws. Parameter studies show differences in system behaviour for improved screw properties; a fuel-controlled vs. ventilation-controlled fire; and different panel thicknesses. Interestingly, as thermal bowing of the panel retards screw failure, and thicker sandwich panels bow less than thinner panels, thicker façade panels will decrease failure time. This and other insights obtained, and the predicted failure of two tiny but critical screws within 80 s, as compared to 150 min lasting sandwich panels in standard fire tests, stresses the need to study complete systems under realistic fires, rather than to study individual components in standard fire tests. Future research will focus on detailed FE models of the connections; full-scale fire experiments; CFD temperature measurement points at the façade outside; detailed modelling of the insulation; and the effects of high temperature creep. Highlights: Sandwich façade fire resistance studied fundamentally, not via tests or codes. For FEM, failure modes for panels, facade openings, and connections (ambient). Temperature dependent properties for steel plates, columns, and sections. Façades under realistic fires should be studied, not their components in tests.